Epidemiology of Spinal Cord Injury in Pakistan: A Retrospective Study - Darain, Haider; Ilyas, Syed Muhammad; Zeb, Amir; Ullah, Irfan; Muhammad, Dildar (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
Background Spinal cord injury has not received robust attention in Pakistan. The only time when the topic was highlighted was earthquake 2005 which struck the northern region of the country. More than 120 000 people lost their lives and a big number of survivors sustained injury to spinal cord.Study Design This was a retrospective trial where data from one of the oldest paraplegic centre was retrieved and analysed.Objectives The objective of this study was to report epidemiology of spinal cord injury in general population of the country.Methods Data regarding patients with spinal cord injury was retrieved from Paraplegic Centre Peshawar from 2011 to 2016. Retrieved data was analysed through SPSS and frequencies were calculated.Results A total of 1 025 patients with mean age 32.6±14.6 years were admitted in the center from 2011 to 2016. The number of male patients was 3 time higher compared to their counterpart female population. Majority (90%) of the patients were paraplegic. Half of the population included were not educated. Majority of the patients were laborer (21.4%) or house wives (21.3%). The common causes for the injury were ‘fall from height’ (30.4%), road traffic accidents (25.5%) and firearm injury (21.1%).Conclusion It can be concluded the causes of spinal cord injury in Pakistan are similar to the causes reported in the majority of studies carried out in other countries. However, firearm injury in spinal cord remained a distinctive cause in the country which has not been reported in the other countries.
Keywords: spinal injury; spinal cord injury (SCI); health care research; Lumbar surgery